Studies of protection and recovery techniques of diagnostic mirrors for ITER. (11th August 2015) - Litnovsky, A.; Matveeva, M.; Buzi, L.; Vera, L.; Krasikov, Y.; Kotov, V.; Panin, A.; Wienhold, P.; Philipps, V.; Castaño Bardawil, D.; Akiyama, T.; Biel, W.; et al.
Abstract: In optical diagnostic systems of ITER, mirrors will be used to guide the light from plasma towards detectors and cameras. The mirrors will be subjected to erosion due to fast particles and to deposition of impurities from the plasma which will affect adversely the mirror reflectivity and therefore must be suppressed or mitigated at the maximum possible extent. Predictive modeling envisages the successful suppression of deposition in the diagnostic ducts with fins trapping the impurities on their way towards mirrors located in the end of these ducts. To validate modeling predictions, cylindrical and cone-shaped diagnostic ducts were exposed in TEXTOR for 3960 s of plasma operation. After exposure, no drastic suppression of deposition was observed in the cylindrical ducts with fins. At the same time, no detectable deposition was found on the mirrors located at the end of cone-shaped ducts outlining the advantages of the cone geometry. Analyses of exposure provide evidence that the contamination of exposed mirrors was due to wall conditioning discharges and not due to working plasma exposure. Cleaning by plasma sputtering was performed on molybdenum mirrors pre-coated with a 100 nm thick aluminum film. Aluminum was used as a proxy of beryllium. During exposure in electron cyclotron resonance-generated helium plasma, the entire coating was sputtered within nine hours, leaving no trace of aluminum and leading to the full recovery of the specular reflectivity without detrimental effects on the mirror surface.